Basic concepts and recent advancements in the study of male fertility - Kovac, Jason R (Asian J Androl, 2016)
Many controversial topics regarding Andrology in general, and male infertility more specifically have been discussed and debated for decades. Numerous manuscripts and entire journals have been dedicated to the dissemination of standardized information with multiple reviews covering similar topics. This massive amount of data leads to difficulty identifying pertinent clinical practice guidelines. Furthermore, detailed instructions on how to manage common clinical conditions tend to be diluted by copious amounts of text and superfluous information.